Estratégia de uso de água salina na irrigação do milho AG 1051 - Galvão, Daniel de Carvalho (2014)
The maize crop is widespread in Brazil. In the state of Rio Grande do Norte, the maize crop is exploited in practically all municipalities in which predominates as the cropping system, the upland, whose water supply is dependent on the rainfall. In arid and semi-arid regions, water intended for irrigation is often contain excess soluble salts, and the use of those waters without proper management, can lead to salinisation of soils, reducing the growth and development of plants. The objective of this study was to evaluate the productivity and the development of hybrid maize AG 1051 irrigated with waters of different salt concentrations applied at different times throughout the crop cycle. The experimental design was randomized blocks with 5 replications and 6 treatments. Agronomic traits of commercial interest such as total yield of ears and commercial with husk corn, overall productivity and commercial without husk, grain yield, aboveground biomass (stem, leaf and fruit) and the increase of soil salinity were evaluated. The treatments consisted of the combination of water with three levels of salinity (S1 - 0.75 dS m-1, water derived from the draw-well, which explores the Açu Sandstone aquifer; S2 - 2,5 dS m-1 and S3 - 5,0 dS m-1) applied at different times (E) along the crop cycle. (E1 - 0 to 30 DAE, E2 - 31 to 60 DAE and E3 - 61 to 90 DAE), resulting in the following treatments (T): T1 - S1, S1, S1, T2 - S1, S2, S2, T3 - S1 , S3, S3, T4 - S2, S2, S2, T5 - S1, S2, S3, T6 - S3, S3, S3. Each term of the sequence is the salinity of times E1, E2 and E3. No significant effect (p <5%) of the treatments was observed in all yield components evaluated, except for the weight of dried corn cobs with and without straw. In general observed decreases in macronutrient content of the soil along the crop cycle. It was also found that irrigation with the most saline treatments, in addition to negatively influence the chemical properties of the soil were those who contributed to the higher accumulation of Na+ and Cl- in plant tissue. Irrigation with water of different salinities at different times can minimize salinity effects for culture